The effect of the angle between fracture line and Kirschner wires on stability in supracondylar humerus fractures treated with Kirschner wire fixation: A finite element analysis - Durusoy, Serhat (Jt Dis Relat Surg, 2021)
OBJECTIVES: This study aims to investigate the effects of the angles created by the Kirschner wires (K-wires), which are applied in the percutaneous fixation of supracondylar humerus fractures with cross K-wire, with the fracture line on fracture stabilization. PATIENTS AND METHODS: The study was conducted on distal humerus fracture models. Medial and lateral K-wires were placed in the fracture models. The angle between the fracture line and the K-wire inserted from medial was represented by alpha (α), while the angle between the fracture line and the K-wires inserted from lateral was represented by beta (β). A combination of various angles (30°, 45°, and 60°) was used in each model, where no two models had the same combination of α and β, resulting in nine different wire configurations. The simulation program was used to simulate the effects of forces, which were applied on rotation, flexion and extension directions, on these models. We measured and compared the stress on the wires and the displacement of fractures under different force configurations. RESULTS: When the force was applied in the counterclockwise direction, the stresses were 58 megaPascal (MPa) on medial K-wire, 24 MPa on lower lateral K-wire, and 45 MPa on upper lateral K-wire in (45°, 45°) wire configuration. When the force was applied in the clockwise direction, the stresses were 57 MPa on medial K-wire, 23 MPa on lower lateral K-wire, and 45 MPa on upper lateral K-wire in (45°, 45°) wire configuration. In all models, the increased α and β angles were translated into the decreased stress on K-wires at the fracture level and decreased displacement under rotational deforming forces. Despite having generally lower fracture displacement, the increased α and β angles led to variable changes in the stress on K-wires against flexion and extension forces. CONCLUSION: In supracondylar humerus fractures, increasing the insertion angle of both medial and lateral K-wires augments stabilization and reduces displacement, particularly against rotational deforming forces.